Design of Purwarupa Actuator on Car-Based Mobile Robot for the Implementation of Application Solution of Path Planning by Using Map Information - Fatahah Dwi Ridhani; Mitra Djamal (Program Pendidikan Vokasi Universitas Brawijaya, 2014)
Path planning and controlling system for car-based mobile robot was applied on a car-based mobile robot with 1/18 scale. This system controlled the car-based mobile robot to reach the target position. The path planning used static Reed-Shepp curvature. The car-based mobile robot was built by modifying R/C model car in order to be controlled by PC (Personal Computer). The additional parts were sensor system to measure the steering angle and the one to measure the steering of traction motor. This robot has been also added with simple control system so the data interchange between mobile robot and computer could be minimized. Lastly, the unit was calibrated to determine characteristics of the car-based mobile robot.